2022
DOI: 10.3389/fmed.2022.832851
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Sleep Disorders and Incidence of Dry Eye Disease in Ningbo: Data From an Integrated Health Care Network

Abstract: PurposeTo investigate the association between sleep disorders and dry eye disease (DED) in Ningbo, China.MethodsOur data came from the Yinzhou Health Information System (HIS), including 257932 patients and was based on a 1:1 matching method (sleep disorder patients vs. patients without sleep disorders) during 2013–2020. Sleep disorders and DED were identified using ICD-10 codes. Cox proportional hazards regression was used to identify the association between sleep disorders and DED.ResultsThe eight-year incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…As an important environmental and lifestyle factor, how sleep pattern plays a role in disease as well as in health has been increasingly under investigation. It has been observed that sleeping is not only associated with many systemic diseases, such as hypertension ( Levenson et al, 2017 ) and coronary heart disease ( Cheng et al, 2014 ; Lao et al, 2018 ), but also with eye diseases, such as diabetic retinopathy ( Tan et al, 2018 ), vision impairment ( Sun et al, 2021 ), dry eye ( Au et al, 2019 ; Zheng et al, 2022 ), myopia and cataract ( Zhou et al, 2023 ). Interestingly, researchers provided evidence that night sleeping hours were associated with the decreased expression of TIMP-3, IER3, and SLC16A8 in AMD patients ( Sharma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an important environmental and lifestyle factor, how sleep pattern plays a role in disease as well as in health has been increasingly under investigation. It has been observed that sleeping is not only associated with many systemic diseases, such as hypertension ( Levenson et al, 2017 ) and coronary heart disease ( Cheng et al, 2014 ; Lao et al, 2018 ), but also with eye diseases, such as diabetic retinopathy ( Tan et al, 2018 ), vision impairment ( Sun et al, 2021 ), dry eye ( Au et al, 2019 ; Zheng et al, 2022 ), myopia and cataract ( Zhou et al, 2023 ). Interestingly, researchers provided evidence that night sleeping hours were associated with the decreased expression of TIMP-3, IER3, and SLC16A8 in AMD patients ( Sharma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…31 A significant positive correlation between poor sleep quality and DED has also been reported, 32,33 as well as an association between sleep disturbances and a threefold increased risk of DED. 34 This evidence suggests that a reciprocal relationship exists between sleep quality and DED.…”
Section: Introductionmentioning
confidence: 99%